2020
DOI: 10.1177/0300985820967449
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV595E Mutation Associates CCL17 Expression and Regulatory T Cell Recruitment in Urothelial Carcinoma of Dogs

Abstract: Regulatory T cells may serve as targets in cancer immunotherapy. A previous study showed that the chemokine CCL17 and the receptor CCR4 play roles in regulatory T cell recruitment in canine urothelial carcinoma. In this article, we show that the BRAFV595E mutation is associated with tumor-produced CCL17 and regulatory T cell infiltration in dogs with urothelial carcinoma. In comparison with healthy dogs, dogs with urothelial carcinoma showed increased CCL17 mRNA expression in the bladder and elevated CCL17 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“… 38 We have recently shown that BRAF V595E mutation induces CCL17 production and contributes to Treg recruitment in dogs with bladder cancer. 36 Thus, we investigated whether BRAF V595E mutation influences tumor-infiltrating Tregs or the CCL17–CCR4 axis in dogs with prostate cancer. Of the 28 dogs with prostate cancer used in this study, BRAF V595E mutation was detected in 21 (75%) cases ( online supplemental table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 We have recently shown that BRAF V595E mutation induces CCL17 production and contributes to Treg recruitment in dogs with bladder cancer. 36 Thus, we investigated whether BRAF V595E mutation influences tumor-infiltrating Tregs or the CCL17–CCR4 axis in dogs with prostate cancer. Of the 28 dogs with prostate cancer used in this study, BRAF V595E mutation was detected in 21 (75%) cases ( online supplemental table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…BRAF V595E mutations were examined by digital PCR assay using genomic DNA isolated from urine sediments, as previously described. 36 …”
Section: Methodsmentioning
confidence: 99%
“…To differentiate between urothelial and prostate carcinoma, a combination of markers will be necessary. In a recent study [131], the chemokine CCL17 was found to contribute to regulatory T cell (Treg) recruitment in prostate tumors. In dogs with prostate cancer, tumor-infiltrating Tregs were found to be associated with bad prognosis [132].…”
Section: Diagnosismentioning
confidence: 99%
“…A somatic point mutation in the BRAF gene (BRAF V595E ), which is homologous to the human BRAF V600E mutation, is present in over 70% of dogs with bladder and prostate cancers (23). We have recently shown that BRAF V595E mutation induces CCL17 production and contributes to Treg recruitment in dogs with bladder cancer (24). Thus, we investigated whether BRAF V595E mutation influences tumor-infiltrating Tregs or the CCL17/CCR4 axis in dogs with prostate cancer.…”
Section: Braf V595e Mutation Correlates With Tumor-infiltrating Tregs and Ccl17/ccr4 Expression In Canine Prostate Cancermentioning
confidence: 99%
“…Urinary CCL17 was assessed by ELISA, as described above. BRAF V595E mutations were examined by digital PCR assay using genomic DNA isolated from urine sediments, as previously described (24).…”
Section: Biomarkersmentioning
confidence: 99%